Foundational research in accounting PARTE 1: professional memoirs and beyonds - Mattessich, Richard (De Computis, Revista Española de Historia de la Contabilidad., 2015)
Foundational research in accounting: professional memoirs and beyonds. PARTE 1 2015 Revision and Extension of the De Computis Edition (of 2006) Richard Mattessich